Specificity, kinetics and longevity of antibody responses to avian influenza A(H7N9) virus infection in humans. Issue 3 (March 2020) - Chen, Junbo; Zhu, Huachen; Horby, Peter W.; Wang, Qianli; Zhou, Jiaxin; Jiang, Hui; Liu, Liwei; Zhang, Tianchen; Zhang, Yongli; Chen, Xinhua; Deng, Xiaowei; Nikolay, Birgit; et al.
Highlights: A(H7N9) patients mounted strong serum HAI antibody responses against A(H7N9) virus. Mean A(H7N9) virus-specific HAI antibody titers remained above 80 for 11 months. Severely ill patients mounted higher HAI antibody responses against A(H7N9) virus. Abstract: Objectives: The long-term dynamics of antibody responses in patients with influenza A(H7N9) virus infection are not well understood. Methods: We conducted a longitudinal serological follow-up study in patients who were hospitalized with A(H7N9) virus infection, during 2013–2018. A(H7N9) virus-specific antibody responses were assessed by hemagglutination inhibition (HAI) and neutralization (NT) assays. A random intercept model was used to fit a curve to HAI antibody responses over time. HAI antibody responses were compared by clinical severity. Results: Of 67 patients with A(H7N9) virus infection, HAI antibody titers reached 40 on average 11 days after illness onset and peaked at a titer of 290 after three months, and average titers of ≥80 and ≥40 were present until 11 months and 22 months respectively. HAI antibody responses were significantly higher in patients who experienced severe disease, including respiratory failure and acute respiratory distress syndrome, compared with patients who experienced less severe illness. Conclusions: Patients with A(H7N9) virus infection who survived severe disease mounted higher antibody responses that persisted for longer periods compared with those that experienced moderate disease. Studies of convalescent plasma treatment for A(H7N9) patients should consider collection of donor plasma from survivors of severe disease between 1 and 11 months after illness onset.